APOS Theory-Based E-LKPD to Improve Adaptive Reasoning of Fourth Grade Elementary School Students - Saraswati, Gusti Ayu Hanny Kurnia; Agustika, Gusti Ngurah Sastra; Margunayasa, I Gede (International Journal of Natural Science and Engineering, 2025)
Although mathematics learning at the Elementary School level has undergone various innovations, many students still have difficulty understanding mathematical concepts. To overcome this problem, a learning media is needed to stimulate students' cognitive activities, such as E-LKPD (Electronic Student Worksheet) based on APOS Theory (Action, Process, Object, Schema), which emphasizes the stages of students' mathematical thinking development. This study aimed to analyze the effectiveness of E-LKPD based on APOS theory (Action, Process, Object, Schema), which is valid, practical, and effective in improving students' adaptive reasoning. The development model used is the ADDIE model. The subjects of this study were 30 fourth-grade students. The trial subjects included lecturers, teachers and students. The data collection methods and instruments used were interviews, observations, questionnaires and tests. Data analysis techniques included quantitative, qualitative and inferential descriptive analysis. The results of this study indicate that E-LKPD media based on APOS theory effectively improves students' adaptive reasoning on mathematical material, picture patterns, and number patterns in fourth-grade students. Based on APOS theory, this study implies that E-LKPD can be an alternative digital learning media that supports meaningful learning and the development of high-level thinking skills from an early age.